Delimitation of the spider genus Sesieutes Simon, 1897, with descriptions of five new species from South East Asia (Araneae: Corinnidae) - Pakawin Dankittipakul (2018)
The spider genus Sesieutes Simon, 1897 is redefined on the basis of both somatic and genital morphology. It is presumably monophyletic and supported by a combined presence of characters. The type species of the genus, Sesieutes lucens Simon, 1897, is redescribed and its conspecific female is described here for the first time. Five new species are described from South East Asia. These taxa are Sesieutes minuatus sp. nov. and Sesieutes aberrans sp. nov. from Thailand, Sesieutes abruptus sp. nov. and Sesieutes bifidus sp. nov. from Malaysia, and Sesieutes apiculatus sp. nov. from Indonesia. Sesieutes borneensis Deeleman-Reinhold, 2001 is recorded from Palawan, the Philippines for the first time, expanding the distribution range of the genus northwards. Sesieutes lucens is recorded from Malaysia for the first time. New records of Sesieutes scrobiculatus Deeleman-Reinhold, 2001 and Sesieutes nitens Deeleman-Reinhold, 2001 have become available from localities other than the type localities. Four species are misplaced in Sesieutes but will be transferred to Jacaena Thorell, 1897 in a separate paper once that genus is redefined and revised. As delimited, the genus comprises 12 species occurring in humid rainforests of the Indo-Burmese and Sundaland of the Oriental Region. A key to all species of Sesieutes is provided. http://www.zoobank.org/urn:lsid:zoobank.org:pub:612E1E8A-1C43-40F8-A146-141D81DFAC62. © 2013 Copyright 2013, Chiang Mai University.